A Review of Coccidioidomycosis in California: Exploring the Intersection of Land Use, Population Movement, and Climate Change. (6th September 2019) - Pearson, Dharshani; Ebisu, Keita; Wu, Xiangmei; Basu, Rupa
Abstract: California has seen a surge in coccidioidomycosis (valley fever), a disease spread by the Coccidioides immitis fungus found in soil throughout the state, particularly in the San Joaquin Valley. We reviewed epidemiologic studies in which outbreak and sporadic cases of coccidioidomycosis were examined, and we considered the possible relationship of these cases to environmental conditions, particularly the state's increasing aridity, drought, and wildfire conditions. Most of the studies we reviewed pertained to cases occupationally acquired in construction, military, archeological, and correctional institutional settings where workers were exposed to dust in C. immitis –endemic areas. A few reviewed outbreaks in the general population related to dust exposure from natural disasters, including an earthquake-associated landslide and a dust storm that carried particles long distances from endemic areas. Although many of California's coccidioidomycosis outbreaks have been occupationally related, changing demographics and new, immunologically naïve populations in dry, endemic areas could expose the general population to C. immitis spores. Given the high rate of infection among workers who, for the most part, are healthy, the general population, including some elderly and immunocompromised individuals, could face additional risk. With climate-related events like drought and wildfires also increasing in endemic areas, research is needed to address the possible associations between these phenomena and coccidioidomycosis outbreaks.